Taphonomic analysis of rodent bone accumulations produced by the White-tailed Kite (Elanus leucurus, Accipitriformes) in Central Argentina - Montalvo, Claudia Inés (2014)
The main objective of this study was to determine the taphonomic characteristics of ingested rodent prey remains recovered from White-tailed Kite (Elanus leucurus, Accipitriformes) pellets. Bones were analyzed in order to identify taphonomic features produced by this predator. Sampling was performed during the austral reproductive season of 2011 in Central Argentina (La Pampa province). The taphonomic variables evaluated suggest that E. leucurus produces strong digestion (categories 4–5). Results and interpretations were compared with results provided by samples from the Black-shouldered Kite, Elanus caeruleus, in Algelia, and from other Falconiformes and Accipitriformes species. The dietary similarity of E. leucurus and Barn Owl (Tyto alba, Strigiformes), suggests that both raptors are dietary counterparts, consuming the same trophic resources alternatively during day and night, but overlapping in their diets. In this context, the role of E. leucurus as fossil or archaeological bone accumulators or as an agent involved on the formation of the deposit might introduce an equifinality problem. The results presented here can be used as an analytical model for the interpretation of the micromammal fossil record from paleontological and archaeological sites.